Breast cancer prevention in districts affected by the Chernobyl nuclear power plant accident beginning from child ages (Environment & Health, 2021)
The aim of this paper was to assess the prevalence of the T risk allele of the MTHFR:677 genetic polymorphism in a group of girls from Ivankovsky and Polessky districts located near the Chernobyl exclusion zone. In addition, we assessed variants of combined carriership of the T allele with risk alleles of other genetic polymorphisms regulating the folate cycle.Research methods. Immunochemical, statistical.Results. Genetic predisposition to breast cancer risk was analyzed in a group of 251 adolescent girls. Carriership of the T allele of the MTHFR:С677Т polymorphism was found in 142 children (56.6%), while the homozygous T/T variant was found in 25 girls, or in 10.0% of cases. Compound heterozygosity for the 677CT/1298AC alleles of the MTHFR gene was recorded in 60 individuals, or in 23.9% of cases.Conclusions. The revealed genetic changes in the folate cycle lead to a significant decrease in the activity of methylenetetrahydrofolate reductase, and, accordingly, to an increase in the level of homocysteine in the blood, creating conditions for the occurrence of breast cancer.Given the high level of genetic predisposition, taking into account the constant impact on the body of radioactive elements and their decay products, the occurrence, as a consequence, of serious metabolic disorders, it is necessary to identify the breast cancer risk group of children.
Keywords: folate cycle; risk alleles; breast cancer; adolescent girls; radiation contaminated areas